THE LEADERSHIP OF REGENT MAWARDI YAHYA IN INFRASTRUCTURE DEVELOPMENT IN OGAN ILIR REGENCY SOUTH SUMATRA 2005-2015: Kepemimpinan Bupati Mawardi Yahya Dalam Pembangunan Infrstruktur di Kabupaten Ogan Ilir Sumatera Selatan 2005-2010 - Muhammad Sultan Fahkhri Arya Sena; Syafruddin Yusuf Yusuf (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study analyzes the leadership of Regent Mawardi Yahya in the infrastructure development of Ogan Ilir Regency, South Sumatra, from 2005 to 2015. Ogan Ilir Regency, a division of Ogan Komering Ilir Regency in 2004, underwent significant transformation under the leadership of Mawardi Yahya, who was also a central figure in the division and held a strategic position within the Golkar Party. The research method used was historical, with heuristics, source criticism, interpretation, and historiography to produce an accurate reconstruction of events. The results show that in the 2005–2010 period, the leadership focused on building the foundations of government through the establishment of bureaucratic structures, the issuance of regional regulations, and the strengthening of institutional and fiscal systems. In the 2011–2015 period, the focus shifted to physical development, including the Tanjung Senai Regional General Hospital, the Tanjung Senai Integrated Office Complex, the An-Nur Grand Mosque, the Sungai Rambutan Independent Integrated City, and the inter-regional road and bridge network. This development improves mobility, access to publicservices, regional connectivity, and economic growth, demonstrating Mawardi Yahya's visionary andeffective leadership, earning him the nickname "Father of Development" of Ogan Ilir Regency.